2016
DOI: 10.3171/2015.12.focus15529
|View full text |Cite
|
Sign up to set email alerts
|

Direct navigated 3D ultrasound for resection of brain tumors: a useful tool for intraoperative image guidance

Abstract: OBJECTIVE Navigated 3D ultrasound is a novel intraoperative imaging adjunct permitting quick real-time updates to facilitate tumor resection. Image quality continues to improve and is currently sufficient to allow use of navigated ultrasound (NUS) as a stand-alone modality for intraoperative guidance without the need for preoperative MRI. METHODS The authors retrospectively analyzed cases involving opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 40 publications
(39 reference statements)
1
54
0
3
Order By: Relevance
“…As it provides instant visualization, USG is not affected by this change and is advantageous than neuronavigation [2,3,7]. USG is not affected by the location changes of tissues during surgery and after resection and this is an important advantage of USG but if craniotomy cannot be made in lesion border, a clear image cannot be provided as the prob movement would be limited [5].…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…As it provides instant visualization, USG is not affected by this change and is advantageous than neuronavigation [2,3,7]. USG is not affected by the location changes of tissues during surgery and after resection and this is an important advantage of USG but if craniotomy cannot be made in lesion border, a clear image cannot be provided as the prob movement would be limited [5].…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
“…In another study on a pediatric patient group, it was shown that the use of intraoperative USG was a faster and more affordable method compared to MRI [14]. The use of USG in residual tissue evaluation due to the imaging quality deficiency was limited before, but today it can prove optimal evaluation in residual tissue with the technological developments and imaging quality improvements [7]. Information can be provided on the vascularity of the present lesion with Doppler USG through instant visualization, and thus surgical area coagulation can be provided more easily during surgery [5].…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
“…Second, highlighted structures are extracted in both imaging modalities by applying the Otsu multi-level thresholding method. Third, segmented structures are combined via a fused rule defined by Equation (1). Finally, a post-processing stage is performed to remove small structures detected that are in general false positives.…”
Section: Image Fusion For Residual Brain Tumor Identificationmentioning
confidence: 99%
“…This intraoperative modality is routinely used to guide brain tumor operations. Particularly, iUS aims at identifying the presence of possible tumor residuals at the end of the operation, in order to remove as much tumor tissue as possible [1,2]. This is a crucial aspect since several studies showed that a gross-total resection has a positive impact on the progression-free survival of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many advanced technologies are widely used in intraoperative brain tumor detection and neurosurgical guidance, including computer tomography (CT) (13), diffusion-weighted magnetic resonance imaging (MRI) (14), fluorescence (15,16) and fluorescence spectral analysis (17), Raman spectroscope (18,19), ultrasound (20), photoacoustic imaging (21), biomarkers (22), and evaporative ionization mass spectrometry (23) etc. OCT can visualize sub-surface tissue structure non-invasively, the micro-meter depth microstructure of tissue also has an intuitive demonstration for neurosurgeons, and the research of neurosurgical OCT are launching gradually in neurosurgical diagnostics and guidance.…”
Section: Introductionmentioning
confidence: 99%